1986
DOI: 10.1128/aac.30.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of clindamycin-resistant anaerobic bacteria isolated from cultures taken following clindamycin therapy

Abstract: MICs of clindamycin were determined by the agar dilution method against anaerobic organisms isolated from endometrial cultures in women with pelvic soft tissue infections. Cultures were obtained from 100 women both before and after clindamycin therapy, from 107 women before therapy with clindamycin or another antimicrobial agent or after treatment with an antimicrobial agent other than clindamycin, and from 9 women 1 to 9 weeks after they were discharged from the hospital following clindamycin therapy. Only 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The emergence of clindamycin resistance following treatment is not a novel finding. In 1986, Ohm-Smith et al reported on the emergence of clindamycin-resistant anaerobic bacteria from the endometria of women with pelvic soft tissue infections (23). As in the present study, they found no correlation between antibiotic resistance and clinical response to therapy.…”
Section: Discussioncontrasting
confidence: 45%
“…The emergence of clindamycin resistance following treatment is not a novel finding. In 1986, Ohm-Smith et al reported on the emergence of clindamycin-resistant anaerobic bacteria from the endometria of women with pelvic soft tissue infections (23). As in the present study, they found no correlation between antibiotic resistance and clinical response to therapy.…”
Section: Discussioncontrasting
confidence: 45%
“…Antibiotic susceptibility patterns of GPAC a Smith et al(206) described selection of clindamycin-resistant anaerobes, particularly GPAC, following clindamycin therapy for pelvic soft tissue infections. Recently, Reig et al(223) andSanchez et al (230) have described inducible macrolide-lincosamide resistance in several species of GPAC; they recommended that erythromycin susceptibility be assessed before individual isolates are reported as susceptible to clindamycin.…”
mentioning
confidence: 99%
“…For 14% of the Peptococcus strains studied by Sutter and Finegold (13), which were isolated from 1972 to 1975 and that would now be classified as Peptostreptococcus strains (4), the clindamycin MIC was >64 ,ug/ml. On the other hand, the selection of clindamycin-resistant Peptostreptococcus strains (up to 64% of the isolates) in the course of clindamycin therapy has been reported (11). Most clinicians were unaware of these data, and therefore, these antibiotics, particularly clindamycin, continue to distance of 10 to 15 mm on plates inoculated with a swab from a bacterial inoculum that was prepared to achieve a turbidity equal to that of no.…”
mentioning
confidence: 99%